2016
DOI: 10.1111/bld.12162
|View full text |Cite
|
Sign up to set email alerts
|

Investigating peer attitudes towards the use of key word signing by children with Down syndrome in mainstream schools

Abstract: Background: Lámh is a key word signing approach used in Ireland, which can support the communication needs of children with Down syndrome. However, the success of this approach in mainstream schools relies heavily on the attitudes of those within the school environment. To date, two studies have explored the attitudes of teaching staff towards the use of keyword signing in schools; however, no previous research has investigated peer attitudes towards this method of communication. This study aimed to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The findings of this project support previous research which found that children enjoy using keyword signs (Bowles and Frizelle 2016) and that Big Books (without signs) are a successful way of engaging young children with stories (Jayendra, Nitiasih, and Mahayanti 2018). The study goes beyond this existing research to show that Sign Supported Big Books are highly valued and enjoyed by teachers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of this project support previous research which found that children enjoy using keyword signs (Bowles and Frizelle 2016) and that Big Books (without signs) are a successful way of engaging young children with stories (Jayendra, Nitiasih, and Mahayanti 2018). The study goes beyond this existing research to show that Sign Supported Big Books are highly valued and enjoyed by teachers.…”
Section: Discussionsupporting
confidence: 83%
“…One rare evaluation examined the attitudes of 6-year-old pupils (without special educational needs) to using Lámh, an Irish keyword signing approach. This study by Bowles and Frizelle (2016) found that all children had a positive attitude towards using this type of signing (Bowles and Frizelle 2016). Mistry and Barnes (2012) evaluated the use of Makaton, a UK keyword sign approach, to support reception class children (approximately 5 years of age), many of whom had English as an Additional Language (EAL).…”
Section: Inclusive Indonesian Classrooms Projectmentioning
confidence: 99%
“…Keyword signing has been introduced to inclusive classrooms in Indonesia, to support pupils with IDs who might previously have been excluded from education (Sheehy and Budiyanto, 2014). Research has identified that people's beliefs about the stigmatization of difference, in relation to children with IDs, can be elicited through their responses to questions about the use, and potential use, of manual signing (Bowles and Frizelle, 2016). The stigmatization of children whose behaviour or appearance makes them look different to their peers, for example, through signing (Sheehy and Duffy, 2009), is a major issue in inclusive education internationally (United Nations Children's Fund, 2012) and a particular issue in Indonesia (Heung and Grossman, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…These issues were particularly pertinent in main stream schools although not exclusive to same. Recent Irish research by Bowles and Frizelle (2016) revealed that teachers struggled trying to adapt to the use of Lámh within the class room setting due to the lack of knowledge in the area. Perceive lack of knowledge is not unique to the Irish education setting, as it has emerged in other contexts with other forms of AAC (De Bortoli et al, 2014;Kent-Walsh and Light, 2009; McNaughton et al, 2008; Singh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%